Age and Awareness as Predictors of Usage Frequency and Advocacy for Mobile Wallets in Nepal - Lamichhane, Basu Dev; Chalise, Mahananda; Dhungana, Bharat Ram (Nepal Journal of Multidisciplinary Research, 2026)
Background: Adoption of mobile wallets is one of the most important features of financial digitization in Nepal. Understanding drivers of their use and promotion is important for long-term development. Objectives: This study was undertaken to (1) investigate the relationship between the age of users and frequency of usage of mobile wallets, and (2) analyze the impact of functional awareness on the likelihood to recommend mobile wallets. Methods: A quantitative cross-sectional study among 216 mobile wallet users in Kathmandu Valley was carried out through convenience sampling. Data was collected using a structured questionnaire and analyzed using descriptive statistics and Kruskal-Wallis H Test on SPSS. Results: The correlation between age and use frequency was statistically significant (p=.001), with the age bracket 21-25 being the most regular users (82.9% used it weekly or daily). A statistical variation in intent to recommend by awareness level was also determined (p=.001), as a hypothesis that a rise in awareness will lead to a higher intention to market the service. Conclusion: The findings confirm that the younger age groups are the key drivers of mobile wallet adoption in Nepal, and that educating users is a critical measure to attain loyalty and word-of-mouth expansion. Implications: Implications of this study are that mobile wallet providers should adopt age-specific marketing strategies to increase adoption rates of their products among various demographic groups. Furthermore, there is a need to increase financial literacy to support national digitalization strategies.